BUILDING EMPLOYEE PERFORMANCE: THE ROLE OF REWARD AND PUNISHMENT MEDIATED BY WORK DISCIPLINE - Ekowati, Vivin Maharani; Supriyanto, Achmad Sani; Permadani, Viola Putri; Fahreza Sani, Ahmad Firza (JIMFE (Jurnal Ilmiah Manajemen Fakultas Ekonomi), 2024)
ABSTRACTThe research aims to test and analyze the effect of reward and punishment on employee performance and determine whether work discipline mediates the effect of reward on employee performance and whether work discipline mediates the effect of punishment on employee performance. The population of this research is PDAM Malang employees, totaling 329 permanent employees. The sample size was determined using the Slovin formula with a precision of 10%, so the sample size was 77 employees. The sample determination method used was simple random sampling. The research method uses Path Analysis. The research results show that reward and punishment do not directly influence employee performance. Work discipline mediates the effect of reward and punishment on employee performance. Work discipline can help employees better understand their work and provide more insight into evaluating their performance. The findings of this research can be applied to improve employee performance by giving rewards and applying punishment through work discipline so that organizational goals can be achieved.ABSTRAKTujuan penelitian adalah untuk menguji dan menganalisis pengaruh reward dan punishment terhadap kinerja karyawan, disiplin kerja memediasi pengaruh reward terhadap kinerja karyawan, dan disiplin kerja memediasi pengaruh punishment terhadap kinerja karyawan. Populasi penelitian ini adalah karyawan PDAM Malang berjumlah 329 pegawai tetap. Jumlah sampel ditentukan dengan menggunakan rumus Slovin dengan presisi 10% maka ukuran sampel adalah 77 orang pegawai. Metode penentuan sampel yang digunakan yaitu simple random sampling. Metode penelitian menggunakan Path Analysis. Hasil penelitian menunjukkan bahwa reward dan punishment tidak memiliki pengaruh langsung terhadap kinerja pegawai. Disiplin kerja memediasi pengaruh reward dan punishment terhadap kinerja pegawai. Disiplin kerja dapat membantu pegawai lebih memahami pekerjaan dan memberikan pemahaman lebih tentang evaluasi atas kinerja mereka. Temuan penelitian ini dapat diaplikasikan untuk meningkatkan kinerja karyawan dengan memberikan penghargaan dan menerapkan hukuman melalui disiplin kerja, sehingga tujuan organisasi dapat tercapai.